DIGITIZATION AND PRESERVATION OF ARCHIVAL DOCUMENTS (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
The digitization of archival documents is a critical development in the management and preservation of historical records. This thesis explores the processes, benefits, and challenges associated with the digitization and preservation of archival materials. It examines various digitization techniques, the role of metadata, and the strategies for ensuring the long-term preservation of digital records. By analyzing case studies and best practices, this research provides insights into effective methods for digitizing and preserving archival documents to ensure their accessibility and longevity.